The CD34+ Cell Dose Matters in Hematopoietic Stem Cell Transplantation with Peripheral Blood Stem Cells from Sibling Donors - M. Remberger; B. Grønvold; M. Ali; J. Mattsson; T. Egeland; K. U. Lundin; A. Myhre; I. Abrahamsen; D. Heldal; I. Dybedal; G. E. Tjønnfjord; T. Gedde-Dahl; et al. (Clinical Hematology International, 2020)
The effect of CD34+ cell dose in allogeneic hematopoietic stem cell transplantation (HSCT) on overall survival (OS) and incidence of acute and chronic graft-versus-host disease (GvHD) has not been established and few studies have been performed. Our single center analysis included 189 patients with hematological malignancies who received peripheral blood stem cell (PBSC) grafts from sibling donors. Myeloablative conditioning was used in 88 cases and 101 received reduced intensity conditioning. The median CD34+ cell dose was 5.6 × 106/kg (0.6–17.0). In the multivariate analysis, a CD34 cell dose of 6–7 × 106/kg was associated with better OS and lower transplant-related mortality (TRM), while a dose of <5 × 106/kg led to increased relapse and reduced chronic GVHD (cGVHD). A high CD34 cell-dose (>6.5 × 106/kg) correlated with less acute GVHD (aGVHD) II–IV. We conclude that the CD34 cell dose has an impact on the outcome of HSCT from sibling donor PBSCs.